Explaining Local Manufacturing Growth in Chile : The Advantages of Sectoral Diversity - Almeida, Rita; Fernandes, Ana M. (Taylor and Francis, 2013)
This article investigates whether the agglomeration of economic activity in regional clusters affects long-run manufacturing Total Factor Productivity (TFP) growth in an emerging market context. We explore a large firm-level panel dataset for Chile during a period characterized by high growth rates and rising regional income inequality (1992–2004). Our findings are clear-cut. Locations with greater concentration of a particular sector have not experienced faster TFP growth during this period. Rather, local sector diversity was associated with higher long-run TFP growth. However, there is no evidence that the diversity effect was driven by the local interaction with a set of suppliers and/or clients. We interpret this as evidence that agglomeration economies are driven by other factors such as the sharing of access to specialized inputs not provided solely by a single sector, e.g. skills or financing.